Pengembangan Lembar Kerja Peserta Didik (LKPD) Bermuatan Kearifan Lokal Suku Sasak pada Mata Pelajaran Pendidikan Pancasila di Kelas IV SDN 1 Korleko Selatan - Iin Juliana; Khairun Nisa; Muhammad Erfan (Mataram University, 2026)
This study aims to develop teaching materials in the form of student worksheets containing local wisdom of the Sasak tribe and to test their validity, practicality, and effectiveness in improving student learning outcomes. This research is a development research with the ASSURE model consisting of 6 stages, namely, 1) analyzing students, 2) formulating learning objectives, 3) selecting methods, media, and teaching materials, 4) utilizing media, technology, and teaching materials, 5) involving student participation, 6) evaluation and revision. The research subjects were 15 fourth-grade elementary school students with the object in the form of teaching materials